2001
DOI: 10.1067/mcp.2001.114926
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous magnesium sulfate for bronchial hyperreactivity: A randomized, controlled, double‐blind study

Abstract: In the magnesium group, 30% of the subjects reached a normal PC(20) compared with 10% in the placebo group. We conclude that intravenous magnesium sulfate significantly improved bronchial hyperreactivity and may serve as an adjunct to standard treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 30 publications
(43 reference statements)
0
8
0
Order By: Relevance
“…A randomized, controlled, and double-blind study demonstrated a significant improvement in methacholine-provoked bronchial hyperreactivity in 30 patients after intravenous MgSO 4 (0.3 mmol ⅐ kg Ϫ1 ⅐ h Ϫ1 ). 127 Several case reports support these findings, one of which describes continuous magnesium infusion to facilitate rapid extubation and recovery in a ventilated patient not responding to standard bronchodilating therapy. 128 Inhaled Magnesium.…”
Section: Mechanisms Of Actionmentioning
confidence: 94%
“…A randomized, controlled, and double-blind study demonstrated a significant improvement in methacholine-provoked bronchial hyperreactivity in 30 patients after intravenous MgSO 4 (0.3 mmol ⅐ kg Ϫ1 ⅐ h Ϫ1 ). 127 Several case reports support these findings, one of which describes continuous magnesium infusion to facilitate rapid extubation and recovery in a ventilated patient not responding to standard bronchodilating therapy. 128 Inhaled Magnesium.…”
Section: Mechanisms Of Actionmentioning
confidence: 94%
“…Some studies have observed its impact on the management of neuritis, deltoid bursitis, and myalgias. 17 , 18 , 19 …”
Section: Introductionmentioning
confidence: 99%
“…These studies have proved that hypomagnesaemia in asthma is associated with increased incidence of wheeze, impairment of lung function, and increased bronchial hyper-reactivity (BHR). As mentioned before, low magnesium level may enhance calcium movement inside the smooth muscle cell and making the cell more contractile and thus increasing BHR [6,7]. Mg deficiency may also increase production of acetylcholine in cholinergic nerve endings, increase histamine release from mast cell, increase production of interlukin-1 and 6, and enhance production of IgE [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Mg has several actions on bronchial airways including bronchodilation, anticholinergic effects, and stabilization of mast cells [4,5]. Hence, Mg deficiency leads to increased contractility of bronchial smooth muscle and increased airways hyperreactivity [6,7].…”
Section: Introductionmentioning
confidence: 99%